ANALISIS PERBEDAAN HARAPAN DAN PERSEPSI KONSUMEN SERTA PENGARUHNYA TERHADAP NIAT BELI ULANG MEMBELI DI TPI REMBANG - Utomo, Trisno; Rizal R, Alimuddin (Jurnal Ilmiah Telaah Manajemen, 2005)
Research about service quality has been done many times, but research of service quality in forming ofrepurchasing intention from merchant of fish at place auction fish is still rare. There fore this research is aimed to test model modification told by Parasuraman et. Al(1998) and Lupioadi(2001) , that is by interacting five variable or dimension of service quality with repurchasing intension measurement of service quality use gap beetwen perceived service with expected service.This research was conducted in REmbang REgency with with Research object of Fiash Auction Place and its subject is merchan of fish. Data was applied in this research was 126 of 150 questioner spreading. Result of this research indicated that there are negative gap beetwen percived service with expected service.Base of the result of this research management of fish auction place require to improve performance of service quality. so that repurchasing intention from merchant of fish in fish auction place can be defended or is even improved thus, managerial implication of this research have beeb tried to be compiled in comprehensive analysis matrix to be able to reference.